Distance-Virtual Education: Development and Characteristics in Mathematics Courses - Sucerquia Vega, Edison Alberto; Londono Cano, Rene Alejandro; Jaramillo Lopez, Carlos Mario; Carvalho Borba, Marcelo de [UNESP] (Fundacion Univ Catolica Norte, 2016)
The distance-virtual learning is a field that permanently transforms itself and allows the creation of new educational programs in different fields of knowledge and educational levels. In this sense currently is conducted a research called Interaction Processes for Producing Mathematical Knowledge in a Student Group with Media in Virtual Distance Learning, aimed at educating a PhD student and contributing to this field with theoretical and methodological perspectives in Mathematical Education in the context of the program of virtual education called Ude@,through a study of qualitative-approach cases. This article deals with some analysis, reflections and significant characteristics of the teaching-learning processes of mathematics in this type of virtual environments, through the proposal of strategies that identify those interaction processes that allow producing mathematical knowledge in virtual-distance-education courses.
Keywords: Virtual distance education; Interaction processes; Mathematical knowledge production